Worker well-being and quit intentions: Is measuring job satisfaction enough? - Diane Pelly (University College Dublin, UCD School of Economics, 2022)
While the links between worker well-being and quit intentions have been well researched, most studies to date rely on a very narrow conceptualisation of well-being, namely job satisfaction, thus ignoring the documented multidimensionality of subjective well-being. This paper explores whether this approach is justified. Using novel survey data, I compare the extent to which hedonic (job satisfaction; positive and negative affect) and eudemonic (disengagement; satisfaction of basic psychological needs at work) well-being indicators individually and jointly explain variation in the quit intentions of 994 full-time UK workers. Well-being indicators perform well overall, explaining four to nine times more variation in quit intentions than wages and hours combined, with the disengagement measure performing best. I find systematic differences in the hedonic and eudemonic well-being profiles of workers who report positive quit intentions and those who do not. A composite model containing all seven indicators offers the best fit, explaining 29.4% of variation in quit intentions versus 24.0% for job satisfaction on its own. My findings suggest that the standard single-item job satisfaction indicator is probably good enough for organisations who are looking for a quick and easy way to identify workers who may be most at risk of forming positive quit intentions. For organisations seeking to develop effective preventative quit strategies however, supplementing single-item job satisfaction with multifaceted well-being indicators is likely to yield valuable additional insights into workers' experiences which can inform the design of targeted interventions.
Keywords: I31; J280; J220; J260; M5; 330; voluntary turnover; quit intentions; employee retention; worker well-being; experienced utility; decision utility; job satisfaction; engagement; affect